Linguistic Diversity and Workplace Productivity - Harald Dale-Olsen; Henning Finseraas (Institute of Labor Economics (IZA), 2019)
We study the importance of linguistic diversity in the workplace for workplace productivity. While cultural diversity might improve productivity through new ideas and innovation, linguistic diversity might increase communication costs and thereby reduce productivity. We apply a new measure of languages' linguistic proximity to Norwegian linked employer-employee Manufacturing data from 2003-12, and find that higher workforce linguistic diversity decreases productivity. We find a negative effect also when we take into account the impact of cultural diversity. As expected proficiency in Norwegian of foreign workers improves since their time of arrival in Norway, the detrimental impact disappears.
Keywords: J15; D24; J24; 330; productivity; diversity; language diversity; GMM